Effect of Monoreagent Delay Time Variation at Room Temperature on Creatinine Levels - Layla Nur Hidayah; Hari Saktiningsih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Creatinine is a waste product of body metabolism that is excreted by glomerular filtration in the kidneys. One method for measuring serum creatinine is the Jaffe Reaction which is based on the reaction between creatinine and picric acid in an alkaline medium, forming a red-orange complex. Creatinine reagents have a shorter shelf life or stability, especially after being mixed into a monoreagent. Monoreagents that are delayed may affect the levels of the analyte being tested. Based on this, the study aims to determine the effect of variations in monoreagent delay time at room temperature on creatinine levels. This research used an analytical experimental design and was conducted in the STIKES Nasional laboratory. A total of 10 samples were obtained using quota sampling from students of class 2A2, D-III Medical Laboratory Technology, STIKES Nasional Surakarta. A total of 30 data points were analyzed using the non-parametric Friedman test. The results showed that the average creatinine levels at 0 minutes, 3 hours, and 4 hours were 0.611 mg/dL, 0.555 mg/dL, and 0.572 mg/dL, respectively. Normality testing indicated the data were not normally distributed, so that the non-parametric Friedman test was used. The test results showed a p-value of 0.014 (p < 0.05), indicating a statistically significant difference. In conclusion, variation in monoreagent delay time at room temperature affects creatinine levels.